A Christmas carol : the original manuscript edition - Dickens, Charles, 1812-1870 (W. W. Norton & Company, 2016)
"A first-ever trade edition of the original manuscript of the beloved Christmas classic. Every year at the holidays, the historic Morgan Library & Museum in Manhattan displays one of the crown jewels of its extraordinary collection: the original manuscript of Charles Dickens's A Christmas Carol, with its detailed emendations, deletions, and insertions in Dickens's own hand. Here, for the first time in a beautiful trade edition, A Christmas Carol: The Original Manuscript Edition presents a facsimile of that invaluable manuscript, along with a typeset version of the story, a fascinating introduction by the Morgan's chief literary curator on the history of the story, and a new foreword by Colm Tóibín celebrating its timeless appeal."--